Undesired effect of excessive betamethasone administration during pregnancy: A rare case - Alireza Mirzaei; Solmaz Piri; Kaveh Gharanizadeh; Mozhdeh Zabihiyeganeh (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Postpartum bilateral femoral neck fracture (BFNF) is a rare condition. We here report a case of BFNF due to excessive corticosteroid consumption, twin pregnancy, immobility, and vitamin D deficiency. Case: This is a report of a 32-yr-old woman with bilateral femoral insufficiency fracture five days after emergency cesarean section due to preterm labor, twin pregnancy, and the history of a previous cesarean section at 33 wk. Antenatal repeated courses of betamethasone injections for fetal lung maturity, daily oral use of prednisolone for the history of miscarriage, immobilization, and vitamin D deficiency were the important contributing factors in her past medical history and lab investigations. The bone mineral density examination showed low bone density for the expected age. Conclusion: Clinicians, who deal with pregnant women, should consider the diagnosis of bilateral femoral insufficiency fracture in any pregnant women with pelvic pain. Awareness of risk factors of BFNF might help to reduce the rate of this complication.